Non-Weight Bearing versus Partial Controlled Early Weight Bearing after Reconstruction of the Fibular Collateral Ligament: A Randomized Control Trial. Issue 7 (30th July 2018) - LaPrade, Robert F.; DePhillipo, Nicholas N.; Cram, Tyler; Cinque, Mark; Kennedy, Mitchell; Dornan, Grant; O'Brien, Luke
Objectives: To 1) determine if early protected weight bearing after an FCL reconstruction was safe based upon an objective difference in laxity on varus stress radiographs at six months postoperatively between patients who were non-weight bearing versus partial controlled weight bearing during the first six weeks of postoperative rehabilitation and 2) determine if there was a difference in pain, edema, and range-of-motion between these two groups at three different time points. Methods: Patients were prospectively enrolled from January 2014 to April 2017. Patients were included in the study if they were undergoing an isolated FCL reconstruction or combined ACL and FCL reconstructions. Patients were randomly assigned to either a control group, which was non-weight bearing for 6 weeks, or a treatment group with partial controlled weight bearing at 40% body weight with crutches for 6 weeks. Patients were excluded if they were less than 18 years of age, pregnant, undergoing a revision FCL reconstruction, concurrent medial collateral and/or posterior cruciate ligament reconstruction, radial or root meniscal repairs, genu varus alignment in patients with chronic FCL tears, or had a body mass index ≥ 35 kg/m 2 . Results: Thirty-nine patients were enrolled in the study, with 6 month follow-up obtained in 36 patients (92%). Twenty-five patients (69.4%) had an acute injury (≤ 6 weeks) and 11 patients (30.6%) had a chronic injury (> 6 weeks). The mean time from injury to surgery was 2.3 ± 1.9 weeks and 41.5 ± 37.4 weeks for acute and chronic patients, respectively. There were no significant differences in patient age (p = .157) or BMI (p = .534) between the control and treatment groups. Postoperatively (0-6 months), there were no complications reported and no surgical re-interventions for ligamentous reconstruction failure or arthrofibrosis in either group. There was a significant difference between the preoperative side-to-side difference (SSD) (2.4 ± 1.0) and postoperative SSD (0.2 ± 1.0) for lateral compartment gapping on varus stress radiographs in all patients (p< .001). For the control group, the lateral compartment SSD on varus stress radiographs was reduced from 2.4 ± 1.1 to 0.1 ± 1.1 from preoperative to 6 months postoperative (p < .001). For the treatment group, the SSD on varus stress radiographs reduced from 2.3 ± 0.8 to 0.2 ± 0.8 from preoperative to 6 months postoperative respectively (p < .001). There were no significant differences between the preoperative SSD and postoperative SSD on varus stress radiographs between the control and treatment groups. All patients demonstrated significant improvements in subjective outcome scores (IKDC, WOMAC pain, WOMAC stiffness, WOMAC physical function, WOMAC total, Lysholm, and Tegner scores) between the preoperative and 6 months postoperative conditions (p < .001). There were no significant differences for the outcome measures of pain, edema, and knee range of motion between control and treatment groups at any time points. Conclusion: There were no significant differences between patients who were non-weight bearing compared to early weight bearing at 6 months postoperatively regarding knee stability, pain, swelling, and range-of-motion. We recommend early partial weight bearing following an isolated FCL reconstruction or when combined with an ACL reconstruction because our study found it did not compromise the integrity of the FCL reconstruction graft.